EN TORNO AL TRATADO "SOBRE LO SUBLIME" DE DIONISIO LONGINO - López Eire, Antonio (Myrtia, 2002)
Two writers share the same “logosphere” if they think, and consequently speak and write, about the same theme with similar or identical words or sentences. That can be proved to be the case of the great literary critics Dionysius of Halicarnassus and Dionysius Longinus, the author of the treatise On the Sublime.